Efecto coadyuvante de la apitoxina natural en los niveles de Ig G, Ig M en el tratamiento del moquillo canino - Molina Molina, Elsa Janeth (2022)
The present investigation, adjuvant effect of the natural apitoxin in the levels of IgG, IgM in the treatment of canine distemper, was carried out in consultation dogs of the urban and rural neighborhoods of the city of Latacunga in the Province of Cotopaxi, with the objective to evaluate the immunomodulatory effect of natural apitoxin, through bee sting as an adjuvant to the treatment of canine distemper, under the experimental method, with 60 dogs of different breeds, ages and sex. The anamnesis, clinical and physical examination of the canines with suspicion of the disease were carried out, and the Rapid Test for distemper was applied, using nasal or ocular secretion; Blood samples were taken in tubes without additive for laboratory analysis by chemiluminescence to determine IgG and IgM; the information of each patient was recorded in an individual clinical file and the data analysis was performed using inferential statistics with completely randomized blocks, based on the Anova test with P value, experimental error with a probability of 5% significance and a confidence level of 95%. Where the probability of significance in the control group, experimental 1 every 24 and experimental 2 every 48 hours on day 1 for IgG registered the P value of (0.86) > 0.05; but on day 21 in experimental group 2 for IgG every 48 hours, an increase in its average was determined (9.3b ±) with a P value of (0.01) < 0.05 on day 21, reflecting a significant difference, which confirms the alternative hypothesis (H1) on the immunomodulatory effect of IgG with the use of apitoxin as an adjuvant treatment in canine distemper. The IgM on days 1 and 21 between the treatments presented a P value of (0.77) and (0.29) > 0.05 respectively.